Si Jagai (Siap, Jemput, Antar, Jaga, dan Peduli): An Innovative Program for Enhancing Health Services in Pangkajene and Islands Regency - Mushlihah Muhayyang; Nur Khaerah; Hamrun Hamrun (Mengeja Indonesia Publisher, 2022)
Si Jagai (Siap, Jemput, Antar, Jaga, dan Peduli) is an innovative program designed to enhance health services in Pangkajene and Islands Regency. The aim of this study is to investigate the program's effectiveness and its impact on the community's health outcomes. A qualitative descriptive approach was employed, with primary and secondary data collected from five informants through observation, interviews, and documentation techniques. The findings revealed that the Si Jagai program offers significant benefits to patients, the Si Jagai team, and the Pangkajene district government, demonstrating high compatibility with the community's needs. The program's trialability has shown advantages in raising public awareness of health issues, contributing to improvements in lifestyles, mindsets, and patterns of action, and ultimately leading to better health outcomes. However, some levels of complexity were identified, with certain individuals remaining apathetic towards disease management. In conclusion, the Si Jagai program serves as an effective model for enhancing health services in Pangkajene and Islands Regency, with its innovative approach and alignment with the community's needs leading to positive impacts on public health. Future efforts should focus on addressing the identified complexities and expanding the program to further improve health services in the region. This study offers valuable insights for policymakers and stakeholders in the health sector, emphasizing the potential of innovative, community-driven solutions to address health challenges and improve overall well-being.